Radium isotopes to trace uranium redox anomalies in anoxic groundwater - Krall, L; Auque-Sanz, L; Garcia-Orellana, J; Trezzi, G; Tullborg, E-L; Suksi, J; Porcelli, D; Andersson, P (Elsevier, 2019)
223Ra, 224Ra, 226Ra, and 228Ra isotopes have been measured in groundwaters from depths ranging 50–900 m in fractured crystalline bedrock (Forsmark, Sweden) to understand the reason for elevated (up to 150 μg/L) aqueous uranium (Uaq) at 400–650 m depth. Ra isotope data is interpreted alongside previously reported 222Rn, 234U, and 238U data, as well as PHREEQC geochemical modelling and uranium mineralogy. A novel, [223Ra/226Ra]GW-based approach (where brackets and “GW” subscript refer to expression of an activity ratio measured from groundwater) to groundwater residence time estimation shows that elevated [Uaq] is most common in Holocene-age groundwaters of marine origin. Although these groundwaters are geochemically reducing, the [223Ra/228Ra]corr (where “corr” subscript refers to a correction applied to compare [223Ra/228Ra]GW to the more commonly reported [226Ra/228Ra]GW) suggest that they interact with U-rich pegmatites containing Proterozoic- and Palaeozoic-age Ca-U(VI)-silicate minerals, which are undersaturated in the present groundwaters. Local aqueous U(VI) can be stabilized in Ca2UO2CO30 complexes at pe-values as low as −4.5 but is susceptible to reduction after a modest decrease in pe-value, alkalinity, or Ca concentration. The [223Ra/228Ra]corr and [224Ra/228Ra]GW also suggest that U(VI)aq precipitates as UO2+X at the interface between marine and non-marine groundwaters. From these data, local [Uaq] is proposed to be governed by on-going water-rock interaction involving old U(VI)-minerals.